Identification of GA20ox2 as a target of ATHB2 and TCP13 during shade response - Son, Ora; Zhang, Chaoyue; Yang, Xiaoyu; Duc, Le Thi; Hur, Yoon-Sun; Nam, Kyoung Hee; Choi, Soon-Young; Cheon, Choong-Ill; Kim, Sunghan (Frontiers in Plant Science, 2023)
The shade avoidance syndrome (SAS) is a collective adaptive response of plants under shade highlighted by characteristic phenotypes such as hypocotyl elongation, which is largely mediated by concerted actions of auxin and GA. We identified ATHB2, a homeodomain-leucine zipper (HD-Zip) domain transcription factor known to be rapidly induced under shade condition, as a positive regulator of GA biosynthesis necessary for the SAS by transactivating the expression of GA20ox2, a key gene in the GA biosynthesis pathway. Based on promoter deletion analysis, EMSA and ChIP assay, ATHB2 appears to regulate the GA20ox2 expression as a direct binding target. We also found that the GA20ox2 expression is under negative control by TCP13, the effect of which can be suppressed by presence of ATHB2. Considering a rapid induction kinetics of ATHB2, this relationship between ATHB2 and TCP13 may allow ATHB2 to play a shade-specific activator for GA20ox by derepressing a pre-existing activity of TCP13.